2010
DOI: 10.1007/s10749-010-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

Modernization of heat exchangers in steam turbine units taking features of their operation at specific thermal power plants into account

Abstract: The authors' experience in the modernization of commercial heat exchangers in steam turbine units is discussed with the individual features of the operation of these exchangers at specific thermal power plants taken into account. The variety of conditions under which heat exchanges operate in specific engineering subsystems requires an individualized approach to the model solutions that have been developed for modernizing these systems. New piping systems for commercial heat exchanges have undergone industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It depends on the following factors: the influence of heat cycles in different directions, the inherent and forced vibrations of the tubes in the bundle and in the apparatus as a whole, the corrosive effect of the cooling water, the natural aging of the material of tubes and tube sheets, etc. [1,2].…”
Section: Methods Of Heat Exchanger Reliability Improvementmentioning
confidence: 99%
See 2 more Smart Citations
“…It depends on the following factors: the influence of heat cycles in different directions, the inherent and forced vibrations of the tubes in the bundle and in the apparatus as a whole, the corrosive effect of the cooling water, the natural aging of the material of tubes and tube sheets, etc. [1,2].…”
Section: Methods Of Heat Exchanger Reliability Improvementmentioning
confidence: 99%
“…The choice of approaches and modern engineering solutions for heat exchangers improvement must meet a number of specifications including the following [1]:…”
Section: Research Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth mentioning that the deterioration of the overall power unit efficiency results in the greater consumption of fossil fuels and consequently higher CO2 emission (as well as that of other pollutants) [2]. Keeping in mind that the improvement of heat exchange processes could have a direct influence on the overall efficiency of a power unit, Ryabchikov et al in [3] suggested a number of specific actions, among which the retrofit of cooling water installations is one of the most important.…”
Section: Introductionmentioning
confidence: 99%
“…In TPT tube systems both oscillation amplitude and stress values (in tube and tube sheet junctions) are lower than in the plain tube apparatuses. So in terms of the TPTs vibration characteristics higher reliability can be achieved by a proper tube partition design in TPT apparatuses according to Ryabchikov et al [1].…”
Section: Introductionmentioning
confidence: 99%